(untitled) - Starks, Joy (Boston, Mass., 2013)
Includes index
Keywords: Adobe Photoshop; Computer graphics; Photography -- Digital techniques; Nhiếp ảnh -- Kỹ thuật số; Image processing -- Digital techniques; Xử lý hình ảnh -- Kỹ thuật số; Đồ họa máy tính